Afectación de los ingresos a consecuencia del covid-2019 en la Cooperativa de Transporte Interprovincial Babahoyo - Aldaz Riera, Tanny Lisbeth (2020)
This case study is based on the administration of income, presenting the way in which it is recognized, which must be classified as income that has been generated by the provision of services, taking into account the essential conditions and also that it presents their economic reality. This work is called ´´EFFECTATION OF INCOME AS A CONSEQUENCE OF COVID-2019 IN THE INTERPROVINCIAL TRANSPORTATION COOPERATIVE BABAHOYO´´, which aimed to analyze how income was affected by the appearance of COVID-2019 that planning They were not executed by the Babahoyo Interprovincial Transport Cooperative, it has 25 active Members who seek to obtain income, providing quality services to users, safeguarding integrity and their safety, the Cooperative lacks policies to promote income, which caused that they develop their activities many times in an empirical way. For the execution of this investigative work, a mixed methodology was used with a descriptive approach through techniques such as direct observation and interviews directed at administrative staff and partners, with a structured instrument of 10 questions and the calculation of variations was applied. monetary and percentage. The most relevant results are directed that the income of each partner was affected as a result of COVID and the economic paralysis that the country suffered in the months of March, April and May. For the purposes of the analysis, a projection was developed using the least squares method to establish how income was affected and what it had repercussions on the institution.